A novel trisamidophosphine ligand and its group(IV) metal complexes - Sietzen, Malte; Wadepohl, Hubert; Ballmann, Joachim (Organometallics, 2014)
A novel trisamidophosphine ligand scaffold has been synthesized and employed to coordinate all of the group(IV) metals. The resulting complexes feature closed half-cage geometries with the phosphorus donor and all three amides binding to the metal. Out of nine complexes of the type [PN3]MX (M = Ti, Zr, Hf; X = NMe2, OTf, CH3), the zirconium derivatives have been studied by X-ray diffraction and shown to exhibit metal-phosphorus distances that are well in range of a coordinative bond. In contrast to its heavier homologues, the titanium methyl species [PN3]TiMe is prone to thermally induced ligand CH activation with concomitant loss of methane.